The Right to Deposits in composition an inheritance - Лещенко, Л. В. (Theory and practice of jurisprudence, 2016)
In the article the problem questions of inheritance of right are analysed on a deposit at a bank (financial institution), with an address to materials of judicial and notarial practice. The methods of disposing of right are probed on a deposit at a bank (financial institution), their feature, including registration of the inherited rights. Correlation of testament and testamentary order of depositor is analysed in a jar (financial institution).